SERVICE QUALITY APPLICATION OF BUTLER ON THE GUEST SATISFACTION AT NYAMAN VILLAS SEMINYAK-KUTA - I Wayan Deny Pranayasa; Ni Putu Somawati; I Ketut Suarja; Nyoman Winia; I Ketut Suarta (Journal of Applied Sciences in Travel and Hospitality, 2018)
The quality of services can be defined as the difference between reality and the expectation of customers for services that they had received. The problem in Nyaman villas is the occupancy of a room that came to a significant decline, to the total number of the occupancy of a room as many as 1.162 people. So, the problem of the research is how the application of the quality of services butler toward satisfaction of customers at Nyaman Villas Seminyak-Kuta? As for the purpose of this research is to know the application of the quality of services of butler toward satisfaction of customers at Nyaman Villas Seminyak-Kuta. The sample techniques in this research were incidental random sampling with a population have to actually representative. So, the number of respondents in this research was = 4 x indicators (4 x 20 = 80 people). The analysis was done with of qualitative and quantitative methods with the approach analysis diagram kartesius. Based on the results of qualitative analysis it can be seen that the average level of customer satisfaction is still relatively low if than the level of hope. Based on the results of the quantitative analysis calculation importance-performance analysis known that the average expectations consumers a whole is 4.42 and the average level of service butler as a whole is 3.89. This indicates 4.42 > 3.89, meaning greater expectations consumers than service butler given by Nyaman Villas or in other words the quality of services they received did not in conformity with expectation consumers.